Efficacy of inspirational motivation on the performance of public health workers in mid-north of Uganda - Emmanuel Komakech; Gilbert Obici; David Mwesigwa (Annals of Human Resource Management Research, 2021)
Purpose: This study sought to determine the efficacy of inspirational motivation on the performance of middle-level Public Health Workers (PHWs) in Lira District Local Government. Specifically, the study aimed to: determine the degree of inspirational motivation among ML-PHWs in Lira District; determine the level of performance among ML-PHWs in Lira District; and investigate the effect of inspirational motivation on the performance of ML-PHWs in Lira District. Research methodology: The study adopted a cross-sectional survey design while incorporating both quantitative and qualitative methods. The study used stratified and simple random sampling procedures to select health facilities, supervisors and ML-PHWs; a total of 164 respondents were selected. Results: The findings suggest that inspirational motivation has a significant effect on the performance of ML-PHWs ( p<0.01). Limitations: This study only focused on one construct of transformational leadership style (inspirational motivation), yet there are several constructs of that style, which may affect the performance of PHWs. Contribution: The findings of this study can be useful to public service managers wishing to enhance the performance of PHWs using limited resources.